A prospective, longitudinal, comparative analysis of the World Health Organization / International Committee of the Red Cross Basic Emergency Care Course on emergency medicine knowledge and confidence among recent medical school graduates - Nichole Michaeli; Andrew Beck; Giovanna De Luca; Mary Gitau; Derek Lubetkin; Derick Ochieng; Grace W. Wanjiku; Justin G. Myers (International Journal of Emergency Medicine)
Abstract Background The Basic Emergency Care (BEC) course was created by the World Health Organization (WHO) in collaboration with the International Committee of the Red Cross (ICRC) and the International Federation for Emergency Medicine (IFEM) to train frontline providers in low-resource settings. This study aims to evaluate long-term retention and maintenance of emergency care knowledge and confidence among University of Nairobi School of Medicine graduates after completing the BEC course. Methods This longitudinal, prospective, comparative study was conducted with recent graduates of the University of Nairobi School of Medicine from October 2021 to May 2023. Participants’ retention of emergency medicine knowledge was assessed comparing a pre/post course test and a multiple-choice examination 12 to 18 months after completing the BEC course. A survey assessed participants’ confidence in managing patients with emergencies 12–18 months after completing the BEC course using a 4-point Likert scale. These results were compared to a control group of recent University of Nairobi School of Medicine graduates who did not take the BEC course. Results The follow-up test scores were lower than the immediate post-course test scores, which suggests some knowledge loss over time. Compared to the control group, the BEC participants had higher test scores during the follow-up period although the difference was not significant. There was no difference between most of the immediate post-course and follow-up survey responses. On follow-up evaluation, BEC participants reported a significant decrease in confidence in understanding emergency drugs and managing an obstructed airway and a patient requiring immobilization. However, compared to the control group, BEC participants had significantly higher self-reported confidence in most areas assessed by the survey. Conclusion The WHO BEC course is effective for emergency care training for medical students at the University of Nairobi. However, the participants’ decrease in knowledge and confidence 12 to 18 months after the BEC course suggests the need for regular refresher courses.